The Construction of Notions on Complex Subjects, in Students of Secondary Education: An Analysis by Means of the Theory of the Conceptual Fields - Silvia Stipcich; Concesa Caballero Sahelices; Marco Antonio Moreira (Universidad Autónoma de Baja California, 2007)
In this paper we discuss and analyze the way in which fifteen-years-old students construct their knowledge when they attend classes regarding gravitational interactions topic, in which a didactic strategy has been used. Such a strategy provided a space to analyze the actions and relationships that constitute the educational experience of a group of students, when they face situations specially designed from the organizing principles of the subject matter, as well as from the characteristics of the involved social group. The study of the conceptualization of gravitational interaction was based in Vergnaud's Conceptual Fields Theory. This theory is very favorable to analyze how people organize the ideas and connect ones with others, to generate new concepts and representations through the years.